Effect of deoxycholic acid on Ca2+ movement, cell viability and apoptosis in human gastric cancer cells. (February 2015) - Chien, Jau-Min; Chou, Chiang-Ting; Liang, Wei-Zhe; Cheng, Jin-Shiung; Chang, Hong-Tai; Tseng, Hui-Wen; Kuo, Soong-Yu; Kuo, Chun-Chi; Chen, Fu-An; Shieh, Pochuen; Ho, Chin-Man; Lin, Jia-Rong; et al.
Abstract Deoxycholic acid (DOA) is one of the secondary bile acids used as a mild detergent for the isolation of membrane associated proteins. This study examined whether the secondary bile acid, DOA, altered Ca2+ movement, cell viability and apoptosis in SCM1 human gastric cancer cells. The Ca2+-sensitive fluorescent dye fura-2 was used to measure [Ca2+]i. DOA-evoked [Ca2+]i rises concentration dependently. The response was reduced by removing extracellular Ca2+. DOA-evoked Ca2+ entry was inhibited by store-operated Ca2+ channel inhibitors (nifedipine, econazole and SKF96365), the protein kinase C (PKC) activator phorbol 12-myristate 13 acetate (PMA) and the PKC inhibitor GF109203X. In Ca2+-free medium, treatment with the endoplasmic reticulum Ca2+ pump inhibitor thapsigargin (TG) abolished DOA-evoked [Ca2+]i rises. Conversely, treatment with DOA abolished TG-evoked [Ca2+]i rises. Inhibition of phospholipase C with U73122 abolished DOA-evoked [Ca2+]i rises. At 100–500 μM, DOA decreased cell viability, which was not changed by chelating cytosolic Ca2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N′, N′-tetraacetic acid-acetoxymethyl ester (BAPTA/AM). DOA between 100 and 300 μM also induced apoptosis. Collectively, in SCM1 cells, DOA-induced [Ca2+]i rises by evoking phospholipase C-dependent Ca2+ release from the endoplasmic reticulum and Ca2+ entry via store-operated Ca2+ channels. DOA also caused Ca2+-independent apoptosis.